ANALYSIS OF METEOROLOGY-OCEANOGRAPHY VARIABILITY IN THE MARITIME CONTINENT OF INDONESIA AND THEIR CONNECTION TO THE MONSOON, ENSO AND DIPOLE MODE INTERACTION - Setiawan, Agus
Abstract: Analysis of some meteorology-oceanography (met-ocean) parameters is done in this research to investigate the atmospheric and oceanic climate variability in the Maritime Continent of Indonesia The parameters used are surface wind (at 10 meter height), surface air temperature, sea surface temperature (SST), sea level pressure (SLP), precipitation rate and outgoing longwave radiation (OLR). The methods to analyze the data are: spatial cross correlation method between the met-ocean parameters above and the SST at NINO3.4, Southern Oscillation Index (SOI) and Dipole Mode Index, wavelet analysis to the cells/regions that have correlation coefficient r >10,31 (r> 0,5 for sea level pressure). Generally found that ENSO phenomena gives a significant contribution to the monsoon variability in the maritime continent of Indonesia i.e. during El-Nino, intensified of southeast monsoon is occurred, while during La-Nina intensified of west monsun is occurred These conditions give rise to the delay of rainy season in the maritime continent of Indonesia during El-Nino (and contrarily accelerate of rainy season during La Nina). The intensified of southeast monsoon (west monsoon) in the maritime continent of Indonesia already occurred 1 to 3 months before the onset of El-Nino (La-Nina). The interaction between ENSO and southeast monsoon in the maritime continent of Indonesia gives a possibility to the occurrence of DM in the Indian Ocean (DM(+) or DM(-)). It is also found that the tropospheric biennial oscillation contribution to the climate variability in the maritime continent of Indonesia is big. This result is agree with another researchs have been done by Yanai et.aL [1998J and Chang [2000].